Relationship between Mother's General Health Status with Quality of Life of Child with Cancer - Shoelh Rahimi; Kolsoom Fadakar Soghe; Rasool Tabari; Ehsan Kazem Nejad Lili (Tehran University of Medical Sciences, 2013)
Background & Aim : Childhood cancer discloses family, and mother in particular, to a number of challenges. It consumes a lot of time, energy, and money of parents to fulfill their caring responsibilities. In some cases and along with increase of caring pressure, mental health of parents deteriorates. The vesting consequences of such events may alter the process of children caring and their quality of life (QoL). The purpose of this study was to examine the relationship between mother's general health status with the QoL of the child diagnosed with cancer.   Methods & Materials : In this descriptive cross-sectional study, 124 mothers of children diagnosed with cancer and aged 6-14 years old, referred to Imam Reza and Amir Hospitals in Shiraz during a four month period (from early November to late February) were selected to the study. Data were gathered using the following instruments: 1) the questionnaire of factors related to QoL in children; 2) mother's general health status form; 3) TNO_AZL Children Quality of Life (TACQOL); and 4) Ped QL Cancer Module. Data were collected through interviewing with mothers and reviewing the medical records of the hospitals. Data were analyzed using the Kruskal-Wallis, Spearman correlation coefficient, Mann-whiteny test and logistic regression in the SPSS-19.   Results: : A few number of mothers (7.3%) reported good general health status and a large number described their general health status as moderate (55.6%) and poor (37.1%). The mean of health related QoL score and the specific QoL score for children were 78.45±10.05 and 65.51±17.54, respectively. According to the multi-factorial logistic regression, demographic and social factors such as child's age and treatment-related factors including the period of radiotherapy, along with the duration of disease were more correlated with health and specific QoL scores in children, compared to the mothers' general health status score.   Conclusion : Results from this study suggested that emotional support is as important as financial empowerment. The QoL in these patients and their families may improve by identifying the families who are at risk of mental problems.